2003
DOI: 10.1091/mbc.e03-03-0193
|View full text |Cite
|
Sign up to set email alerts
|

PIG-W Is Critical for Inositol Acylation but Not for Flipping of Glycosylphosphatidylinositol-Anchor

Abstract: Many cell surface proteins are anchored to a membrane via a glycosylphosphatidylinositol (GPI), which is attached to the C termini in the endoplasmic reticulum. The inositol ring of phosphatidylinositol is acylated during biosynthesis of GPI. In mammalian cells, the acyl chain is added to glucosaminyl phosphatidylinositol at the third step in the GPI biosynthetic pathway and then is usually removed soon after the attachment of GPIs to proteins. The mechanisms and roles of the inositol acylation and deacylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 41 publications
1
80
0
1
Order By: Relevance
“…cerevisiae, an acyl chain is added to the 2-position of inositol early in the GPI biosynthetic pathway (24). The acylation is mediated by PIG-W in mammalian cells (5) and by Bwt1p, the PIG-W orthologue, in S. cerevisiae (25). The acceptor substrate for these acyltransferases is glucosaminyl-phosphatidylinositol (26,27).…”
Section: Gpi Inositol Deacylation In Trypanosoma Bruceimentioning
confidence: 99%
See 2 more Smart Citations
“…cerevisiae, an acyl chain is added to the 2-position of inositol early in the GPI biosynthetic pathway (24). The acylation is mediated by PIG-W in mammalian cells (5) and by Bwt1p, the PIG-W orthologue, in S. cerevisiae (25). The acceptor substrate for these acyltransferases is glucosaminyl-phosphatidylinositol (26,27).…”
Section: Gpi Inositol Deacylation In Trypanosoma Bruceimentioning
confidence: 99%
“…In contrast, precursors of the GPI-anchor present in the endoplasmic reticulum (ER) are resistant to PI-PLC due to an acyl chain linked to the 2-position of inositol (4). The inositol ring of GPI is acylated at an early step in GPI biosynthesis by the action of PIG-W protein, an acyltransferase that adds a palmitoyl chain to the inositol of glucosaminyl-phosphatidylinositol, the second intermediate in the pathway (5). The inositol acylation is critical for the attachment of GPI to proteins, because mutant cells defective in PIG-W express only very low levels of GPI-APs (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type 3B2A cells (22) were cultured in Ham's F12 medium (Sigma). All mutant cell lines [M2S2 (accumulating N-acetyl glucosamine-PI; GlcNAc-PI) (22), CHOPA10.14 (accumulating GlcN-PI) (23), and Lec15 (accumulating GlcN-acyl-PI) (24)] were cultured in Ham's F12 medium supplemented with 10% fetal calf serum and 600 mg/ml G418.…”
Section: Cells and Materialsmentioning
confidence: 99%
“…This reaction is performed by PIG-W (its yeast homolog is named Gwt1p, and the names of the functional homologous proteins in budding yeast are henceforth shown like (yeast Gwt1p)) (30,31). Membrane topological analysis of yeast Gwt1p has shown that acylation of inositol is performed on the luminal side of the ER membrane (32).…”
Section: C-2 Inositol Deacylationmentioning
confidence: 99%